Cultural Resistance: Indonesian Society’s Efforts to Maintain Local Identity Amid Colonial Domination - Siska, Felia; Nafian , Zidni Ilman; Asnimawati; Wijaya, Wibi (SOSEARCH : Social Science Educational Research, 2025)
This article discusses cultural resistance carried out by Indonesian society in facing colonial domination, especially by the Dutch, which attempted to erode local identity through various assimilation policies. With the background of colonial history, this article reviews forms of cultural resistance that are manifested in efforts to maintain language, tradition, art, and nationalist movements. Local education and traditional arts, such as wayang and gamelan, are used as effective symbolic resistance tools in raising nationalist awareness. The national movement also shows the collaboration between culture and politics as a means of resistance against colonialism. Indonesian society developed resilience strategies through cultural adaptation and negotiation, where local values ​​are maintained despite foreign influences. This article emphasizes that cultural resistance not only maintains identity but also forms the basis of national consciousness that plays an important role in the struggle for independence.